A Dual Role for Abscisic Acid Integrating the Cold Stress Response at the Whole-Plant Level in Iris pseudacorus L. Growing in a Natural Wetland - Caselles, Vicent; Casadesús, Andrea; Munné-Bosch, Sergi (Frontiers in Plant Science, 2021)
Leaf senescence, the last stage of the developmental program of leaves, can be induced by both internal and external signals. Cold stress-induced leaf senescence is an efficient strategy to overcome winter temperatures. In this work, we studied leaf senescence in yellow flag (Iris pseudacorus L.) individuals growing in a natural wetland, not only considering its relationship with external and internal cues, but also the plant developmental program, and the biological significance of rhizomes, storage organs that remain viable through winter. Total chlorophyll contents and the maximum efficiency of PSII (Fv/Fm ratio) decreased in senescing leaves, which was associated with a sharp increase in abscisic acid (ABA) contents. Furthermore, total cytokinin and 2-isopentenyladenine contents decreased in December compared to November, as plants became more stressed due to a decline in air temperatures. ABA increases in senescing leaves increased in parallel to reductions in violaxanthin. Rhizomes also accumulated large amounts of ABA during winter, while roots did not, and neither roots nor rhizomes accumulated 9-cis-epoxycarotenoids, thus suggesting ABA, which might play a role in conferring cold tolerance to this subterranean organ, may result from phloem transport from senescing leaves. It is concluded that (i) leaf senescence is a highly regulated physiological process in yellow flag playing a key role in the modulation of the entire plant developmental program, and (ii) ABA plays a major role not only in the regulation of leaf senescence but also in the establishment of cold tolerance in rhizomes, two processes that appear to be intimately interconnected.